Cofilin is a cAMP effector in mediating actin cytoskeleton reorganization and steroidogenesis in mouse and human adrenocortical tumor cells. (10th October 2017) - Peverelli, E.; Catalano, R.; Giardino, E.; Treppiedi, D.; Morelli, V.; Ronchi, C.L.; Vaczlavik, A.; Fusco, N.; Ferrero, S.; Bertherat, J.; Beuschlein, F.; Chiodini, I.; et al.
Abstract: cAMP pathway plays a major role in the pathogenesis of cortisol-producing adrenocortical adenomas (CPA). cAMP-induced steroidogenesis is preceded by actin cytoskeleton reorganization, a process regulated by cofilin activity. In this study we investigated cofilin role in mediating cAMP effects on cell morphology and steroidogenesis in adrenocortical tumor cells. We demonstrated that forskolin induced cell rounding and strongly reduced phosphorylated (P)-cofilin/total cofilin ratio in Y1 (−52 ± 16%, p < 0.001) and human CPA cells (−53 ± 18%, p < 0.05). Cofilin silencing significantly reduced both forskolin-induced morphological changes and progesterone production (1.3-fold vs 1.8-fold in controls, p < 0.05), whereas transfection of wild-type or S3A (active), but not S3D (inactive) cofilin, potentiated forskolin effects on cell rounding and increased 3-fold progesterone synthesis with respect to control (p < 0.05). Furthermore, cofilin dephosphorylation by a ROCK inhibitor potentiated forskolin-induced cell rounding and steroidogenesis (2-fold increase vs forskolin alone). Finally, we found a reduced P-cofilin/total cofilin ratio and increased cofilin expression in CPA vs endocrine inactive adenomas by western blot and immunohistochemistry. Overall, these results identified cofilin as a mediator of cAMP effects on both morphological changes and steroidogenesis in mouse and human adrenocortical tumor cells. Highlights: cAMP induced cell rounding and steroidogenesis in adrenocortical tumor cells. cAMP reduced cofilin phosphorylation in adrenocortical tumor cells. Cofilin silencing impaired cAMP effects on cytoskeleton and steroidogenesis. S3A cofilin transfection or cofilin dephosphorylation potentiated cAMP effects. CPA show increased cofilin expression and reduced P-cofilin/total cofilin vs EIA.